Telling tales : work, narrative and identity in a market age - Lait, Angela (Manchester University Press, 2012)
Telling Tales explores the narrative construction of identity within organisations and how this is resisted and challenged by writing coming from other lifestyles. Since the early 1990s, US-inspired changes in workplace culture have radically altered the experience of UK workers. This book argues that the corporate communication supporting these changes, which seeks to align employee behaviour and attitudes with emerging organisational market values, is having a powerful and harmful effect on those whose identity rests in opposing qualitatively-based occupational standards. By focusing on accountability measures, introduced to the public sector post-1997 by New Labour as a means to raise productivity and lower cost, and with forensic attention to a supporting transformational identity discourse, author Angela Lait shows how workers struggle to achieve the satisfaction and fulfilment at work that was once the mainstay of their professional middle class identity. Reading these identity problems into and across business self-help manuals, fiction (Ian McEwan's Saturday), the writing of celebrity chefs (Nigella Lawson, Jamie Oliver et al) and autobiography, the argument traces a sickness/recovery dialectic in which sufferers find resistance and solace through engagement with particular types of creative labour. These are, most notably, cookery, gardening and writing, which each employ alternative language and narrative forms that order experience according to more regulated rhythms and rituals, and more productive and stable relationships than are possible in paid employment. Telling Tales is a highly-readable, engaging, broad-ranging and interdisciplinary story that will have strong appeal to academics, particularly in literature, sociology, organisational and cultural studies. It will also resonate with anyone trying to reconcile the conflicting work and personal needs of a hectic twenty-four/seven modern world.